Metabolic syndrome in patients with chronic plaque psoriatic disease: a case-control study from western Uttar Pradesh, India - Jain, Shailendra Kumar; Jain, Preeti; Singh, Abhishek; Goel, Shewtank (International Journal of Research in Medical Sciences, 2018)
Background: Various studies on psoriasis and metabolic syndrome have shown a large variation in their results. An increasing frequency is imposing a substantial burden on the overall health of psoriasis patients that needs to be appropriately foreseen and addressed. Aim of this study was to study various aspects of metabolic syndrome in patients with chronic plaque psoriatic disease in northern Indian region. Methods: A cohort of patients registering for treatment of chronic plaque psoriasis at Dermatology outpatients’ department formed the study population. Detailed history was captured. General physical examination was carried out. A thorough cutaneous examination was undertaken which captured details on type, distribution and arrangement of primary lesions and secondary changes in patients. After overnight fasting, venous blood samples were collected from the subjects and were analysed for serum glucose, triglyceride and HDL-cholesterol. Results: Metabolic syndrome in psoriasis was associated with higher age. Gender wise male preponderance was observed. Among the psoriasis cases, 64% had metabolic syndrome whereas among the control subjects 48% had the condition (p-value 0.158). The mean for serum triglyceride level for psoriasis patients (159.42 mg/dL) was higher than controls (144.25 mg/dL). Forty six percent of cases fulfilled elevated triglycerides ≥150 mg/dl as a criterion of metabolic syndrome, compared to 40% of controls. Conclusions: We observed a higher frequency of metabolic syndrome among psoriasis cases in a northern Indian population. An association of dyslipidemia with psoriasis was also noted. Routine screening of the condition to facilitate early diagnosis and treatment should be undertaken.